Modulation of innate and acquired immune responses by Escherichia coli heat-labile toxin: distinct pro- and anti-inflammatory effects of the nontoxic AB complex and the enzyme activity - MILLS, KINGSTON; O'NEILL, LUKE ANTHONY JOHN (The American Association of Immunologists, 2000)
We have examined the roles of enzyme activity and the nontoxic AB complex of heat-labile toxin (LT) from Escherichia coli on its adjuvant and immunomodulatory properties. LTK63, an LT mutant that is completely devoid of enzyme activity, enhanced Th1 responses to coinjected Ags at low adjuvant dose. In contrast, LTR72, a partially detoxified mutant, enhanced Th2 responses and when administered intranasally to mice before infection with Bordetella pertussis suppressed Th1 responses and delayed bacterial clearance from the lungs. LTR72 or wild-type LT inhibited Ag-induced IFN- production by Th1 cells, and LT enhanced IL-5 production by Th2 cells in vitro. Each of the toxins enhanced B7-1 expression on macrophages, but enhancement of B7-2 expression was dependent on enzyme activity. We also observed distinct effects of the nontoxic AB complex and enzyme activity on inflammatory cytokine production. LT and LTR72 suppressed LPS and IFN- induced TNF- and IL-12 production, but enhanced IL-10 secretion by macrophages in vitro and suppressed IL-12 production in vivo in a murine model of LPS-induced shock. In contrast, LTK63 augmented the production of IL-12 and TNF-. Furthermore, LTK63 enhanced NF-B translocation, whereas low doses of LTR72 or LT failed to activate NF-B, but stimulated cAMP production. Thus, E. coli LT appears to be capable of suppressing Th1 responses and enhancing Th2 responses through the modulatory effects of enzyme activity on NF-B activation and IL-12 production. In contrast, the nontoxic AB complex can stimulate acquired immune responses by activating components of the innate immune system.
PUBLISHED
Keywords: Biochemistry